Simultaneous Quantitative Assessment of Ochratoxin A, Patulin, 5-Hydroxymethylfurfural, and Bisphenol A in Fruit Drinks Using HPLC with Diode Array-Fluorimetric Detection - Hassan, N.H. (MDPI, 2020)
The analysis of regulated contaminants in fruit drinks often requires suitable validated and rapid analytical methods for cost-effective food control, and is of considerable interest among the fruit beverage industry. This study demonstrated a rapid and sensitive high-performance liquid chromatography approach for the simultaneous determination of ochratoxin A (OTA), patulin (PAT), 5-hydroxymethylfurfural (HMF), and bisphenol A (BPA) in various fruit drinks. The separations were achieved using a C18 core-shell column with both photo-diode array and fluorimetric detections connected in series. A gradient system consisting of methanol and 0.1 formic acid at a flow rate of 1.2 mL minâ1, thermostated at 35â¦ C, provided fast elution with run time <9 min. Sample pretreatment was optimised to enable extraction of all analytes from fruit drink matrices. The optimised method was validated. Correlation coefficients of R > 0.99 were achieved with detection limits of 0.5 ng mLâ1 (OTA), 1.1 ng mLâ1 (PAT), 7.9 ng mLâ1 (HMF), and 1.0 ng mLâ1 (BPA). Recoveries ranged from 82 to 99. Good relative standard deviations for intraday retention times (â¤3.54) and peak area (â¤3.5) were achieved. The developed multi-contaminants analysis method was successfully applied to determine OTA, PAT, HMF, and BPA in various fruit drinks. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.